2019
DOI: 10.1101/643908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular and Molecular Probing of Intact Transparent Human Organs

Abstract: Optical tissue transparency permits cellular and molecular investigation of complex tissues in 3D, a fundamental need in biomedical sciences. Adult human organs are particularly challenging for this approach, owing to the accumulation of dense and sturdy molecules in decadesaged human tissues. Here, we introduce SHANEL method utilizing a new tissue permeabilization approach to clear and label stiff human organs. We used SHANEL to generate the first intact transparent adult human brain and kidney, and perform 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Before delving into specific details of comparing different protocols, it is essential to provide a brief introduction to the strategies that have been employed in the field (Yau et al, 2023): 1) Increasing antibody (Ab) availability: This involves elevating antibody concentrations or reducing antibody depletion by temporarily inhibiting antibody-antigen binding (Murray et al, 2015;Susaki et al, 2020;Lai et al, 2022). 2) Enhancing tissue diffusivity: This strategy focuses on increasing effective diffusivity in the tissue through elevating tissue permeability (Renier et al, 2014;Zhao et al, 2020) or reducing the distance for diffusion (Cai et al, 2019;Ku et al, 2020). 3) Advective transport of antibodies: this innovative approach involves increasing antibody transport through advective methods, such as electrophoresis (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Before delving into specific details of comparing different protocols, it is essential to provide a brief introduction to the strategies that have been employed in the field (Yau et al, 2023): 1) Increasing antibody (Ab) availability: This involves elevating antibody concentrations or reducing antibody depletion by temporarily inhibiting antibody-antigen binding (Murray et al, 2015;Susaki et al, 2020;Lai et al, 2022). 2) Enhancing tissue diffusivity: This strategy focuses on increasing effective diffusivity in the tissue through elevating tissue permeability (Renier et al, 2014;Zhao et al, 2020) or reducing the distance for diffusion (Cai et al, 2019;Ku et al, 2020). 3) Advective transport of antibodies: this innovative approach involves increasing antibody transport through advective methods, such as electrophoresis (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SPIM requires samples to be optically clear which is time-consuming and often introduces tissue distortion (Dodt et al, 2007;Renier et al, 2014;Jensen and Berg, 2017;Wan et al, 2018;Qi et al, 2019; Figure 3C). Clearing technology itself also limits the size of the sample as it is difficult to remove lipids/penetrate larger volumes such as those of non-human primates and human brains (Tainaka et al, 2018;Zhao et al, 2019;Ueda et al, 2020a; Figure 3C). Even if these brains could be cleared, it is challenging to create an objective lens with a long enough working distance to collect signals from the entire sample (Ueda et al, 2020a).…”
Section: Spimmentioning
confidence: 99%
“…Combining tissue clearing with immunohistochemistry and light‐sheet microscopy, a fully 3D mapping of organs at the cellular and even molecular level can be obtained. There are several tissue‐clearing protocols such as CLARITY, [ 125 ] 3DISCO [ 126 ] and, more recently, SHANEL [ 127 ] that can provide greater volumetric information at the cellular level on intact organs. We foresee that such tissue clearing processes will converge with biofabrication through the digitization of discrete tissue at this cellular and volumetric level.…”
Section: Implications Of Future Hybrid Fabrication Technologiesmentioning
confidence: 99%
“…Interestingly, deep learning and neural networks have been applied to the analysis and understanding of such treated tissues. Excellent research articles [125][126][127] describing in-depth such tissue clearing methods and reviews [128,129] can be found elsewhere.…”
Section: Increasing Complexity Of Scaffolds and Tissue Constructs Wit...mentioning
confidence: 99%